2003
DOI: 10.1086/345437
|View full text |Cite
|
Sign up to set email alerts
|

Population‐Based Surveillance and a Case‐Control Study of Risk Factors for Endemic Lymphocutaneous Sporotrichosis in Peru

Abstract: Population-based surveillance and a case-control study were conducted in Abancay, Peru, to estimate the burden of disease and to determine risk factors for sporadic lymphocutaneous sporotrichosis (LS). Laboratory records from local hospitals were reviewed for the years of 1997 and 1998, and prospective surveillance was conducted for the period of September 1998 through September 1999. A case-control study was conducted with 2 matched control subjects per case patient. The mean annual incidence was 98 cases per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
0
19

Year Published

2003
2003
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 29 publications
7
50
0
19
Order By: Relevance
“…In the south of the American continent the disease more frequently occurs in the humid autumn or in summer (Mackinnon et al 1969, Lopes et al 1999, whereas in Mexico the highest incidence is observed in cold and dry seasons (González-Ochoa 1965). No seasonal difference, however, has been reported by other authors (Vismer and Hull 1997, Lyon et al 2003, Barros et al 2004.…”
Section: Epidemiologymentioning
confidence: 73%
See 1 more Smart Citation
“…In the south of the American continent the disease more frequently occurs in the humid autumn or in summer (Mackinnon et al 1969, Lopes et al 1999, whereas in Mexico the highest incidence is observed in cold and dry seasons (González-Ochoa 1965). No seasonal difference, however, has been reported by other authors (Vismer and Hull 1997, Lyon et al 2003, Barros et al 2004.…”
Section: Epidemiologymentioning
confidence: 73%
“…In some regions, the difference in the distribution of cases according to age and gender might be explained by the type of fungal exposure (Fukushiro 1984, Kusuhara et al 1988, Lyon et al 2003, but no association has been found in other regions (Pappas et al 2000).…”
Section: Epidemiologymentioning
confidence: 99%
“…Es endémica en Sudáfrica 8 , India 9 , Japón 10 , Estados Unidos de América (E.U.A.) 11 y en varios países de Latinoamérica como Perú [12][13][14] , Brasil 5,15 , México 16,17 , Colombia 18 , Uruguay, Costa Rica y Guatemala 19 .…”
Section: Introductionunclassified
“…En estos países, su distribución por sexo y edad está relacionada a la ocupación y exposición al hongo 12,15 . En Brasil la enfermedad estuvo relacionada al contacto con gatos, lo que ha contribuido de manera importante en la forma de transmisión de esporotricosis 5,15,20 .…”
Section: Introductionunclassified
“…Epidemics have been described in western Australia, China and the large outbreak occurred in gold mines of South Africa in more than 3000 miners who had frequent physical contact with wood timber supports. In Uruguay, armadillo hunting is a high-risk activity [5].…”
Section: Discussionmentioning
confidence: 99%